ANALYSIS OF ELECTROENCEPHALOGRAPHY (EEG) SIGNALS USING THE WIRELESS EEG SYSTEM IN OPEN/CLOSED EYES WITHOUT/WITH EM RADIATION INTERFERENCE FROM MOBILE PHONES - Safitri, Nadhila
Electroenchephalography (EEG) is a method used to record the brain's electrical activity on the scalp. The aims of this study is to analyze the effect of open/ closed yes with/without interference from electromagnetic waves (EM) from mobile phones on the power spectral density (PSD) of the measured brain waves. The subjects selected were 6 undergraduate students male aged 20-22 years and did not have a history of mental illness or brain disorders. Brain wave measurements were performed using the Emotiv EPOC+ EEG type with 14 active electrodes and 2 reference electrodes. The voltage versus time data which recorded are the data in (.edf) format and then processed using MATLAB software to do the centering, filtering and Welch's periodogram processes so that the PSD value of the brain waves is obtained. After analyzing the processed data, it was found that the PSD value in closed eyes was higher than in open eyes, both when given electromagnetic interference (2.83 times higher) or without electromagnetic interference (3.71 times higher). The lobe that has the gretest PSD increment was the occipital lobe, which is the vision center in the brain. Meanwhile, the PSD value of the experiment without EM interference had insignificant results with the experiment using EM disorders for open eye conditions and closed eye conditions.